Membangun Identitas Nasional Rusia di Ruang Digital: Analisis Diskursus Narasi Budaya pada Platform Media Negara - Yusril Ihza Mahendra (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines how Russian state-controlled digital media construct national identity through interlinked discursive strategies in the digital sphere. Using Critical Discourse Analysis and a multimodal approach, the research analyzes 2022–2024 content from RT, TASS, and RIA Novosti, focusing on cultural narratives embedded in news articles, features, and multimedia. Findings reveal three dominant narrative frames: (1) historical and civilizational continuity, particularly the mobilization of Great Patriotic War memory and Soviet legacy to legitimize current policies; (2) external threat framing, portraying the West as an adversarial force to reinforce in-group solidarity; and (3) cultural diplomacy, projecting Russia as a resilient, sovereign civilization through heritage preservation, international festivals, and non-Western partnerships. These strategies operate consistently across platforms, suggesting centralized coordination in aligning state identity objectives with mediated public perception. The study contributes to theoretical debates on digital authoritarianism, memory politics, and soft power by demonstrating how multimodal discourse integrates history, security, and culture into a cohesive national narrative. While limited to three major platforms, the methodological framework offers applicability for comparative studies in other national contexts. The findings underscore the role of digital media as a strategic site of identity engineering in contemporary statecraft.